Novel Psychoactive Substances—Recent Progress on Neuropharmacological Mechanisms of Action for Selected Drugs - Hassan, Zurina; Bosch, Oliver G.; Singh, Darshan; Narayanan, Suresh; Kasinather, B. Vicknasingam; Seifritz, Erich; Kornhuber, Johannes; Quednow, Boris B.; Müller, Christian P. (Frontiers in Psychiatry, 2017)
A feature of human culture is that we can learn to consume chemical compounds, derived from natural plants or synthetic fabrication, for their psychoactive effects. These drugs change the mental state and/or the behavioural performance of an individual and can be instrumentalized for various purposes. After the emergence of a novel psychoactive substance (NPS) and a period of experimental consumption, personal and medical benefits and harm potential of the NPS can be estimated on evidence base. This may lead to a legal classification of the NPS, which may range from limited medical use, controlled availability up to a complete ban of the drug form publically accepted use. With these measures, however, a drug does not disappear, but frequently continues to be used, which eventually allows an even better estimate of the drug’s properties. Thus, only in rare cases there is a final verdict which is no more questioned. Instead, the view on a drug can change from tolerable to harmful, but may also involve the new establishment of a desired medical application to a previously harmful drug. Here we provide a summary review on a number of NPS for which the neuropharmacological evaluation has made important progress in recent years. They include mitragynine (“Kratom”), synthetic cannabinoids (e.g., “Spice”), dimethyltryptamine and novel serotonergic hallucinogens, the cathinones mephedrone and methylone, ketamine and novel dissociative drugs, gamma-hydroxybutyrate, gamma-butyrolactone, and 1,4-butanediol. The current review shows emerging harm potentials, but also some potential medical applications.